O livro religioso, em particular do âmbito da parenética e hagiologia, nos impressos do século XVI da Biblioteca Pública do Porto - Marques, João Francisco (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
During the study of this inventory, it was very interesting to learn about the number of works from foreign authors, either written in Latin or Spanish, both languages familiar to the Portuguese readers, as well as vernacular translations published in Portugal during the 16th century. The diversity of themes shows two important cultural aspects: fi rstly, that there were enough readers to justify printing these quite expensive works, the tax paid by each copy being a good source to evaluate their selling price; secondly, the specifi city themes of the books printed reveal diverse interests by the readers.